20 group forms (Journal of Parents and Teachers, 1995)
The article discusses the importance of communication and creativity in group learning, highlighting the need to structure activities that encourage the active participation of all members. Various didactic techniques to facilitate collaborative teaching and learning are mentioned.
Keywords: communication; creativity; participation; collaborative